Social engineering : a discourse in applied social science - Pocock, Louis John (Not Specified, 2024)
[ page 92, 93, 94 missing] The following is a general overview of methodology. For a detailed examination in this area see Appendix III. The methodology of this work is based upon a modified Versteen principle. The present writer gathered 'evi- . 1 dence' and gave it form until it became clear where that evidence led. The evidence was then formalised until it resulted in cogent patterns. The patterns were expanded until they achieved solidity, at which point attempts were made to destroy them by bombarding them with data. To the writer's gratification, they did not collapse under the onslaught. Rather they gained in weight and explanatory power. The patterns were then pruned so as to leave nothing but their fundamental essence. Illustrative modes were then selected on the basis explained in the overview chapter in order to give the patterns substance and the patterns were grounded in terms of and by means of example. The result is the present work.